Physician Advocacy: Identifying Motivations for Work Beyond Clinical Practice: Physician Advocacy - Warwick, Sophia; Kantor, Laura; Ahart, Erin; Twist, Katie; Mabry, Terrance; Stoltzfus, Ky (Kansas Journal of Medicine, 2022)
Introduction. Advocacy is a perceived social and professional obligation of physicians, yet many feel their training and practice environment don’t support increased engagement in advocacy. The aim of this qualitative project was to delineate the role advocacy plays in physicians’ careers and the factors driving physician engagement in advocacy. Methods. We identified physicians engaged in health advocacy in Kansas through personal contacts and referrals through snowball sampling. They received an email invitation to participate in a short in-person or phone interview which was recorded using Apple Voice Memos and Google Dictation. Two team members independently identified themes from interview transcripts, while a third member served as a moderator if themes identified were dyssynchronous. Results. Of the 19 physicians invited to participate, 13 were interviewed. The most common reasons for engaging in advocacy included the desire to change policy, obligation to go beyond regular clinic duties, giving patients a voice, and avoiding burnout. Physicians reported passion for patients and past experiences with disparities as the most common inspiration. Most physicians did not have formal advocacy training in school or residency, but identify professional societies and peers as informal guides. Common support for advocacy were professional organizations, community partners, and employers. Time was the most common barrier to conducting advocacy work. Conclusions. Physicians have a broad number of reasons for the importance of doing advocacy work, but identify key professional barriers to further engagement. Providing accessible opportunities through professional organizations and community partnerships may increase advocacy participation.